2022
DOI: 10.3389/fphar.2022.877872
|View full text |Cite
|
Sign up to set email alerts
|

Erigeron breviscapus (Vant.) Hand-Mazz.: A Promising Natural Neuroprotective Agent for Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is the most common neurodegenerative disease and is characterized by progressive cognitive dysfunction and memory loss in the elderly, which seriously affects the quality of their lives. Currently, the pathogenesis of AD remains unclear. Molecular biologists have proposed a variety of hypotheses, including the amyloid-β hypothesis, tau hyperphosphorylation hypothesis, cholinergic neuron injury, inflammation caused by an abnormal immune response, and gene mutation. Drugs based on these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 106 publications
(105 reference statements)
0
7
0
Order By: Relevance
“…EBI exhibits pharmacological effects of promoting blood circulation, removing blood stasis, dredging collaterals, and relieving pain (Sun and Zhao, 2009). It has been widely used in the treatment of ischemic stroke, coronary heart disease, and angina, and is recorded in the 2020 edition of Pharmacopoeia of the People's Republic of China (ChP 2020) (Wang et al, 2018;Dong and Qu, 2022). Recent studies have suggested that the active ingredients in EBI have potential antitumor effects.…”
Section: Introductionmentioning
confidence: 99%
“…EBI exhibits pharmacological effects of promoting blood circulation, removing blood stasis, dredging collaterals, and relieving pain (Sun and Zhao, 2009). It has been widely used in the treatment of ischemic stroke, coronary heart disease, and angina, and is recorded in the 2020 edition of Pharmacopoeia of the People's Republic of China (ChP 2020) (Wang et al, 2018;Dong and Qu, 2022). Recent studies have suggested that the active ingredients in EBI have potential antitumor effects.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous metabolites are still undiscovered due to the limits of experimental settings and analytical techniques. Therefore, further research on EBHM metabolites is necessary [ 18 ].…”
Section: Active Ingredients and Pharmacological Effects Of Ebhmmentioning
confidence: 99%
“…Previous research has established the precise mechanism of EBHM and its active components in the treatment of Alzheimer’s disease. Dong and Qu demonstrated that EBHM and its active substances (scutellarin, baicalin, and CQA) improved learning memory in animal models of Alzheimer’s disease, and the mechanism may be related to inhibition of Aβ aggregation, modulation of the cholinergic nervous system, reduction of tau protein hyperphosphorylation, resistance to oxidative stress and inflammation, and apoptosis resistance [ 18 ]. However, research on the specific mechanism of EBHM and its active components in the treatment of DCD is lacking.…”
Section: Anti-dcd Effects Of Ebhmmentioning
confidence: 99%
“…This plant is distributed in Hunan, Guangxi, Guizhou, Sichuan, Yunnan, and Tibet provinces in China. It can only be seen in some open slope grasslands and forest margins at altitudes of 1200–3500 m [ 1 ] and has been listed as a nationally protected species of traditional Chinese medicine. The chemical components in E. breviscapus mainly include flavonoids, caffeoyls, coumarins, lignans, terpenoids, and other components [ 2 ], among which scutellarin has the highest content.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, E. breviscapus is of great significance for recovery and secondary prevention after the first onset of cardiovascular and cerebrovascular diseases. In addition, E. breviscapus is a natural neuroprotective agent for Alzheimer’s disease [ 1 ]. At present, according to different doses and routes of administration of E. breviscapus extract, various dosage forms have been developed, such as tablets, capsules, oral liquids, and injections, and international research on E. breviscapus unilateral preparations has also begun.…”
Section: Introductionmentioning
confidence: 99%